Methods for Producing Metal-Organic Framework Extrudates
Patent Information
- Application Number
- JP2022530831
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-26
- Filing Date
- 2020-07-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-07-27
Smart Images

Figure 0007637681000004 
Figure 0007637681000005 
Figure 0007637681000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates generally to metal-organic framework ("MOF") extrudates. More specifically, the present disclosure relates to methods for producing MOF extrudates that maintain the structural integrity of the MOF material and enhance the mechanical strength of the MOF extrudates. [Background technology]
[0002] Materials with large internal surface areas defined by pores or channels are of primary interest for applications such as catalysis, absorption and / or adsorption techniques, ion exchange, chromatography, and substance storage and / or uptake.
[0003] Among the various strategies to create microporous and / or mesoporous active materials, the formation of metal-organic frameworks (MOFs) using metal ions and organic molecular building blocks is particularly advantageous. MOF materials offer many advantages, including (i) larger pore sizes than currently used zeolites, (ii) higher internal surface areas than currently used porous materials, (iii) a wide range of tunable pore sizes and / or channel structures, and (iv) facile functionalization of the organic framework components on the internal surfaces.
[0004] MOFs are hybrid materials in which metal ions or clusters are coordinated to multitopic organic linkers and self-assemble to form coordination networks. These materials have the potential to be used in a wide variety of applications, including gas storage, gas separation, catalysis, sensing, and environmental remediation. In many of these applications, shaped particles are often used to avoid large pressure losses in the reactor bed or to facilitate material handling. The shaping of the material can embody a variety of shapes, including extrudates, rings, pellets, and spheres. To limit the generation of fines during shipping and use, the shaped particles must have sufficient mechanical strength to withstand the compressive forces generated by the process conditions and by the pressure exerted by the weight of the catalyst bed. However, extrusion of materials comprising MOFs is a relatively unexplored field that is needed to compound these novel materials for versatile applications.
[0005] During extrusion, MOFs can be damaged by conditions such as high pressure and temperature, and binders are often required to improve the mechanical strength of the extrudate, but many binders are incompatible with MOFs, primarily due to the lack of a compatible surface.
[0006] Therefore, there is a need for methods of producing MOF extrudates without compromising the structural integrity of the MOF material, and for methods of improving the mechanical strength of MOF extrudates. Summary of the Invention
[0007] The present disclosure relates to a method for producing metal-organic framework extrudates using one or more extrusion aids to reduce pressure during the extrusion process and maintain the structural integrity of the metal-organic framework, and the method can improve the mechanical strength of the metal-organic framework based extrudates.
[0008] Provided herein is a method for producing a metal-organic framework extrudate in an extruder, comprising: (a) mixing a metal-organic framework material with an extrusion aid to form a metal-organic framework extrudate mixture; and (b) extruding the metal-organic framework mixture in an extruder to produce a metal-organic framework extrudate, wherein the pressure in the extruder is about 10% to about 55% lower than the pressure in the extruder when extruding the metal-organic framework material without the extrusion aid. To As described, the extrusion aid may be a liquid extrusion aid, a solid extrusion aid and / or a polymer extrusion aid. The liquid extrusion aid may be a linear C3-C 10 Alkyl alcohol or branched C3-C 10 It may be an alkyl alcohol. In an embodiment, the liquid extrusion aid is selected from the group consisting of 1-propanol, iso-propanol, 1-butanol, iso-butanol, 1-hexanol, and 1-heptanol. In an embodiment, the liquid extrusion aid comprises water in the range of about 0.5% to 95% by volume.
[0009] Solid extrusion aids include graphite, magnesium stearate, or saturated or unsaturated C 10+ It may include an organic acid or a salt thereof. In an embodiment, the solid extrusion aid is mixed with the metal-organic framework in a range of about .5% to about 30% by weight.
[0010] The polymeric extrusion aid may be a polyvinylamide, polyacrylate, polycarbonate, polyamide, polyester, polyether, polyvinylamine, polyvinyl alcohol, polyvinyl ester, or a combination thereof. In an embodiment, the polymeric extrusion aid is polyvinyl alcohol. In one embodiment, the metal-organic framework mixture comprises about 0.5% to 10% by weight of polyvinyl alcohol. The metal-organic framework mixture may comprise polyvinyl acetate and water. In an embodiment, the ratio of polyvinyl acetate to water is about 1:1 to about 1:3.
[0011] The metal-organic framework extrudates can be in the form of rods, ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycomb bodies, or granules. The metal-organic framework extrudates produced by the present method can have a comparative BET surface area of about 40% to about 100%. In an embodiment, the metal-organic framework is HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, MOF-274, or a combination thereof. In an embodiment, the metal-organic framework has a pore size of about 2 Å to about 50 Å. The metal-organic framework extrudates produced by the present method can have a comparative BET surface area of about 40% to about 100%.
[0012] In embodiments, the method further comprises aging the metal-organic framework extrudates at a temperature of about 20° C. to about 100° C. for a period of about 30 minutes or more. In embodiments, the method further comprises activating the metal-organic framework extrudates at a temperature of about 100° C. to about 300° C. for about 1 hour or more. In embodiments, the extruding of the metal-organic framework extrudates is performed through a die having a diameter of about 0.01 mm to about 50 mm. In embodiments, the metal-organic framework extrudates can be washed with any solvent. [Brief description of the drawings]
[0013] [Figure 1] 1 is a powder X-ray diffraction (hereinafter "PXRD") pattern of the HKUST-1 sample of Example 1 extruded with a long chain alcohol. [Diagram 2] 1 shows the N2 adsorption isotherm of HKUST-1 sample of Example 1 extruded with long chain alcohol. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Before describing the extrudates and extrusion methods of the present disclosure in further detail, a list of terms is provided below to aid in a better understanding of the present disclosure.
[0015] All numerical values within the specification and claims are modified by "about" or "approximately" with respect to the indicated value to account for experimental error and variations that would be expected by one of ordinary skill in the art.
[0016] Room temperature is approximately 25° C. unless otherwise specified.
[0017] For the sake of brevity, only certain ranges are explicitly disclosed herein. However, just as a range from any lower limit can be combined with any upper limit to describe a range not explicitly described, a range from any lower limit can be combined with any other lower limit to describe a range not explicitly described. Also, a range includes every point or individual value between its endpoints, even if not explicitly described. Thus, every point or individual value can be combined with any other point or individual value or other lower or upper limit as its own lower or upper limit to describe a range not explicitly described.
[0018] As used in this disclosure and claims, the singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates otherwise.
[0019] As used herein, the term "and / or" as used in expressions such as "A and / or B" is intended to include "A and B," "A or B," or "A" and "B."
[0020] The term "aqueous medium" refers to a liquid that contains 5% or more by volume of water. Suitable aqueous media can comprise or consist essentially of water or a mixture of water and a water-miscible organic solvent.
[0021] term" Extrusion ( Extrusion ) "Molding" refers to the process of forcing a flowable mixture of ingredients through a die of the desired cross-section.
[0022] The term "extrudate" means the elongated body produced during extrusion.
[0023] The term "pre-crystallization (Pre-crystallization) The term "pre-synthesized" refers to materials, particularly metal-organic framework materials, that are pre-synthesized (pre-assembled). formation ), usually the material is formation This means that the reaction medium is separated from the reaction medium in which it is dissolved.
[0024] The term "paste" refers to a solvated powder that has a dough-like appearance and consistency.
[0025] As used herein, the term "metal-organic framework material" or "MOF material" refers to a metal or metalloid and an organic ligand that can be coordinated to the metal or metalloid. In certain embodiments, the MOF coordination network of the organic ligands and the metal (or metalloid) forms a porous three-dimensional structure.
[0026] As used herein, the term "MOF extrudate" refers to extruded MOF material. MOF extrudates comprise one or more metal-organic framework materials that have been treated with at least one extrusion aid, and can further include optional solvents and other additives such as binders, pore formers, lubricants, rheological aids, and other materials that contribute to stability (e.g., metal powders).
[0027] In general, metal-organic frameworks (MOFs) are a relatively new type of highly porous material that is expected to be applied in a wide range of fields, such as gas storage, gas and liquid separation, isomer separation, waste removal, and catalysis. While zeolites are purely inorganic, MOFs use organic ligands to act as "pillars" that bridge metal atoms or metal atomic groups. MOFs, like zeolites, are materials with micropores. The shape and size of the pores in MOFs can be adjusted by selecting the organic ligands and metals. Because MOFs can be modified with organic ligands, they have a variety of structures that are different from zeolites as a whole. Factors that affect the structure of MOFs include, for example, the ligands Denticity, size and type of coordinating group, additional substitutions at or near the coordinating group, size and shape of the ligand, hydrophobicity or hydrophilicity of the ligand, choice of metal and / or metal salt, choice of solvent, reaction conditions such as temperature, concentration, etc.
[0028] MOFs are synthesized or commercially available as loose microcrystalline powder materials. For many industrial and commercial products, it is desirable to mold the powdered MOFs into larger coherent bodies of a defined shape. Traditionally, when powdered MOFs are consolidated into larger bodies by methods such as pelletizing or extrusion, they often have unfavorable physical and mechanical properties. Specifically, when powdered MOFs are compressed and processed, the pressure sensitivity of the MOF structure can result in fairly low BET surface areas and relatively low crush strengths (compressive strengths). Furthermore, improper processing conditions can lead to full or partial phase transformations of the initial MOF structure, as evidenced by powder X-ray diffraction and BET surface area analysis. Each of these factors can be problematic in producing MOF extrudates in the form of compacts and / or in using these compacts in various applications.
[0029] Although it is desirable to consolidate metal-organic framework (MOF) powder materials into a more coherent (shaped) body comprising metal-organic framework material ("MOF material"), the properties of MOF materials, particularly their weakness to pressure and shear, can lead to the collapse of at least some of the pores in the MOF structure, for example during high pressure (e.g., from about 100 psi to several thousand psi) and shear used to consolidate powdered MOFs, particularly during extrusion, leading to an undesirable, often significant, reduction in BET surface area. The conditions for consolidating powdered MOFs into a compact can lead to at least partial, and in some cases complete, conversion of the MOF structure into another material, such as another crystalline phase. Concatenations of MOFs (such as MOF extrudates) can suffer from low crush strength. For example, low crush strength values can lead to fine powders, which can be disadvantageous in certain applications.
[0030] Thus, the present disclosure provides a method for producing MOF extrudates with reduced MOF deformation, increased MOF surface area, and increased crush strength (compressive strength). The method combines one or more extrusion aids with MOF material to produce the MOF extrudates. Extrusion aids useful in the method can include one or more of a liquid extrusion aid, a solid extrusion aid, and / or a polymeric extrusion aid.
[0031] The method of producing MOF extrudates of the present disclosure can include agitating a mixture of pre-crystallized MOF powder material (MOF material) and extrusion aids to form a dough (premix) or paste suitable for extrusion processing. In some cases, agitation by mulling (friction mixing) is performed. Mulling is distinguished from milling in that it does not apply constant pressure and requires less force (energy) during mixing. Mulling does not usually impart enough energy to the MOFs to promote complete conversion of the MOF structure to another crystalline phase. Some MOFs are unstable even to moderate energy inputs, and slight formation of new crystalline phases may occur even under the mild mulling conditions disclosed herein.
[0032] The MOF materials disclosed herein can be characterized in terms of their porosity. The MOF materials can include micropores, mesopores, macropores, and any combination thereof. Micropores are defined herein as having a pore size of about 2 nm or less, and mesopores are defined herein as having a pore size of about 2 nm to about 50 nm. Interparticle texture voids may also be present.
[0033] Desirably, the MOF extrudates formed according to the disclosure herein retain at least a substantial majority of the BET surface area of the metal-organic framework powder material from which they were formed prior to crystallization. Specifically, the metal-organic framework material in the MOF extrudates may be characterized by a BET surface area of about 50%, 60%, 70%, 80%, 90% or more relative to the BET surface area of the metal-organic framework powder material prior to crystallization. Advantageously and surprisingly, in some instances, the BET surface area of the metal-organic framework linked material in the extrudates may even be greater than the BET surface area of the metal-organic framework powder material prior to crystallization. Pelletized samples may exhibit values approaching the BET surface area of the metal-organic framework linked material.
[0034] As described herein, the MOFs can be ZIFs (or Zeolitic Imidazolate Frameworks), MILs (or Laboisier Materiaux), and IRMOFs (or IsoReticular Metal Organic Frameworks), alone or in combination with other MOFs. In some embodiments, the MOFs can be selected from HKUST-1, MOF-74, MIL-100, ZIF-7, ZIF-8, ZIF-90, UiO-66, UiO-67, MOF-808, or MOF-274.
[0035] MOFs can be prepared through a combination of organic ligands or one or more organic ligands and a metal or metalloid, as described below. For example, MOF-274 is a cationically linked metal complex consisting of Mg 2+ , Mn 2+ , Fe 2+ , Zn 2+ , Ni 2+ .Cu 2+ , Co 2+ or a combination thereof with 4,4'-dihydroxy-(1,1'-biphenyl)-3,3'-dicarboxylic acid. Additionally, MOF-274 can include amines within its structure coordinated to metal sites.
[0036] As used herein, "isotherm" refers to the adsorption of an adsorbate as a function of concentration while the temperature of the system is held constant. In an embodiment, the adsorbate is CO2 and the concentration can be measured as CO2 pressure. As described herein, isotherms can be performed with porous materials using various mathematical models applied to calculate the apparent surface area. S. Brunauer, P. H. Emmett and E. Teller, J. Am. Chem. Soc. 1938, 60, 309-319; K. Walton and R. Q. Snoor, J. Am. Chem. Soc. 2007, 129, 8552-8556; I. Langmuir, J. Am. Chem. Soc. 1916, 38, 2221. organic ligand
[0037] As used herein, an organic ligand refers to a ligand that is monodentate, bidentate, polydentate, or a combination thereof. In general, an organic ligand is capable of coordinating to a metal ion, and in principle any compound suitable for such coordination can be used. An organic ligand may include at least two centers capable of coordinating to a metal ion of a metal salt, or capable of coordinating to a metal or metalloid. In some embodiments, the organic ligand includes i) an alkyl group moiety having 1-10 carbon atoms, ii) an aryl group moiety having 1-5 aromatic rings, or iii) an alkyl or arylamine moiety consisting of an alkyl group having 1-10 carbon atoms or an aryl group having 1-5 aromatic rings, where the moiety has at least two functional groups "X" covalently bonded thereto, where X is capable of coordinating to a metal or metalloid.
[0038] In some embodiments, each X is CO2H, OH, SH, NH2, CN, HCO, CS2H, NO2, SO3H, Si(OH)3, Ge(OH)3, Sn(OH)3, Si(SH)4, Ge(SH)4, Sn(SH)3, PO3H, AsO3H, AsO4H, P(SH)3, As(SH)3, CH(RSH)2, C(RSH)3, CH(RNH2)2, C(RNH2)3, C H(ROH)2, C(ROH)3, CH(RCN)2, C(RCN)3, CH(SH)2, C(SH)3, CH(NH2)2, C(NH2)2, CH(OH)2, C(OH)3, CH(CN)2, C(CN)3, nitrogen-containing heterocycles, sulfur-containing heterocycles, and combinations thereof, where R is an alkyl group having 1 to 5 carbon atoms or an aryl group consisting of 1 to 2 phenyl rings. Neutral or ionic form of are independently selected from
[0039] In some embodiments, the organic ligands include substituted or unsubstituted, mono- or polynuclear aromatic di-, tri-, and tetracarboxylic acids, and substituted or unsubstituted, aromatic di-, tri-, and tetracarboxylic acids containing at least one heteroatom, which may have one or more nuclei.
[0040] In some embodiments, the organic ligand is selected from the group consisting of benzenetricarboxylate (BTC) (one or more isomers), ADC (acetylene dicarboxylate), NDC (naphthalene dicarboxylate) (any isomer), BDC (benzene dicarboxylate) (any isomer), ATC (adamantane tetracarboxylate) (any isomer), BTB (benzene tribenzoate) (any isomer), MTB (methane tetrabenzoate), ATB (adamantane tricarboxylate), and the like. R benzoate) (any isomer), biphenyl-4,4'-dicarboxylate, benzene-1,3,5-tris(1H-tetrazole), imidazole or a derivative thereof, or a combination thereof.
[0041] Ligands with multidentate functional groups can be coupled to the corresponding countercations, e.g., H + , Na + , K + , Mg 2+ ,Ca 2+ , Sr 2+ , ammonium ion, alkyl-substituted ammonium ion, aryl-substituted ammonium ion, or a counter anion, such as F - , Cl - ,Br - , I - , ClO - , ClO2 - , ClO3 - , ClO4 - , O.H. - , NO3 - , NO2 - , SO4 2- , SO3 2- , PO4 3- , CO3 2- etc. may be included.
[0042] In some embodiments, the organic ligand comprises a monodentate functional group. A monodentate functional group is defined as a moiety attached to a moiety that can form only one bond to a metal ion, which may include an organic ligand or an amine ligand moiety L as defined above. By this definition, a ligand can comprise one or more monodentate functional groups. For example, cyclohexylamine and 4,4'-bipyridine are said to be ligands that comprise a monodentate functional group, since each functional group can only bind to one metal ion.
[0043] Thus, cyclohexylamine is a monofunctional ligand containing a monodentate functional group, and 4,4'-bipyridine is a bifunctional ligand containing two monodentate functional groups. Specific examples of ligands containing monodentate functional groups include pyridine, a monofunctional ligand, hydroquinone, a bifunctional ligand, and 1,3,5-tricyanobenzene, a trifunctional ligand.
[0044] Monodentate and polydentate functionalized ligands can be blended to make MOF materials in the presence of suitable metal ions and, optionally, a template agent. Monodentate ligands can also be used as template agents. A template agent may be added to the reaction mixture to occupy pores in the resulting MOF material. The monodentate ligands and / or template agents may include the following substances and / or derivatives thereof: A. Alkyl or aryl amines or phosphines and their corresponding ammonium or phosphonium salts. The alkyl amines or phosphines may contain linear, branched, or cyclic aliphatic groups (and their corresponding ammonium salts) having 1 to 20 carbon atoms, and the aryl amines or phosphines may contain 1 to 5 aromatic rings, including heterocycles. Examples of monofunctional amines are methylamine, ethylamine, n-propylamine, iso-propylamine, n-butylamine, sec-butylamine, iso-butylamine, tert-butylamine, n-pentylamine, neo-pentylamine, n-hexylamine, pyrrolidine, 3-pyrroline, piperidine, cyclohexylamine, morpholine, pyridine, pyrrole, aniline, quinoline, isoquinoline, 1-azaphenanthrene, and 8-azaphenanthrene. Examples of di- and trifunctional amines are 1,4-diaminocyclohexane, 1,4-diaminobenzene, 4,4'-bipyridyl, imidazole, pyrazine, 1,3,5-triaminocyclohexane, 1,3,5-triazine, 1,3,5-triaminobenzene. B. Alcohols containing an alkyl or cycloalkyl group containing 1 to 20 carbon atoms or an aryl group containing 1 to 5 phenyl rings. Examples of monofunctional alcohols are methanol, ethanol, n-propanol, iso-propanol, allyl alcohol, n-butanol, iso-butanol, sec-butanol, tert-butanol, n-pentanol, iso-pentanol, sec-pentanol, neopentanol, n-hexanol, cyclohexanol, phenol, benzyl alcohol and 2-phenylethanol. Examples of difunctional and trifunctional alcohols are 1,4-dihydroxycyclohexane, hydroquinone, catechol, resorcinol, 1,3,5-trihydroxybenzene, 1,3,5-trihydroxycyclohexane. C. Ethers containing an alkyl or cycloalkyl group containing 1 to 20 carbon atoms, or an aryl group containing 1 to 5 phenyl rings. Examples of ethers are diethyl ether, furan, and morpholine. D. Thiols containing an alkyl or cycloalkyl group containing 1-20 carbon atoms or an aryl group containing 1-5 phenyl rings. Examples of monofunctional thiols are thiomethane, thioethane, thiopropane, thiocyclohexane, thiophene, benzothiophene, and thiobenzene. Difunctional and trifunctional thiols are 1,4-dithiocyclohexane, 1,4-dithiobenzene, 1,3,5-trithiocyclohexane, and 1,3,5-trithiobenzene. E. Nitriles containing an alkyl or cycloalkyl group containing 1 to 20 carbon atoms, or an aryl group containing 1 to 5 phenyl rings. Examples of monofunctional nitriles are acetonitrile, propanenitrile, butanenitrile, n-valeronitrile, benzonitrile, p-tolunitrile. Examples of difunctional and trifunctional nitriles are 1,4-dinitrilocyclohexane, 1,4-dinitrilobenzene, 1,3,5-trinitrocyclohexane, 1,3,5-trinitrobenzene. F. Inorganic anions from the group consisting of sulfate, nitrate, nitrite, sulfurous acid, bisulfite, phosphate, hydrogen phosphate, dihydrogen phosphate, diphosphate, triphosphate, phosphorous acid, chloride, bromide, iodide, carbonate, bicarbonate, thiocyanide and isonitrile, and the corresponding acids and salts of said inorganic anions. G. Organic Acids and Their Corresponding Anions (and Salts). Organic acids may include alkyl organic acids having linear, branched, or cyclic aliphatic groups and 1 to 20 carbon atoms, or aryl organic acids having 1 to 5 aromatic rings, which may include a heterocycle, and aryl organic anions and salts thereof. H. Other organic and inorganic substances such as ammonia, carbon dioxide, methane, oxygen, ethylene, hexane, benzene, toluene, xylene, chlorobenzene, nitrobenzene, naphthalene, thiophene, pyridine, acetone, 1-2-dichloroethane, methylene hydrochloride, tetrahydrofuran, ethanolamine, triethylamine, or trifluoromethylsulfonic acid.
[0045] Additionally, the template agent may include other aliphatic and aromatic hydrocarbons that do not contain functional groups, hi some embodiments, the template agent includes cycloalkanes, such as cyclohexane, adamantane, or norbornene, and / or aromatics, such as benzene, toluene, or xylene. Metal ions
[0046] As mentioned above, MOFs can be synthesized (produced) by combining metal ions, organic ligands, and, optionally, a suitable templating agent. Suitable metal ions include metals and metalloids of various coordination geometries and oxidation states. In some embodiments, MOFs are produced using metal ions with distinct coordination geometries in combination with ligands with multidentate functional groups and a suitable templating agent. MOFs can be prepared using metal ions that prefer octahedral coordination, such as cobalt(II), and / or metal ions that prefer tetrahedral coordination, such as zinc(II). MOF materials can be prepared by combining metal ions with corresponding metal salt counterions, such as cobalt(II), zinc(II), and / or zinc(II). Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ , Sc 3+ , Y 3+ , Ti 4+ , Zr 4+ , Hf 4+ , V 4+ , V 3+ , V 2+ , Nb 3+ , Ta 3+ , Cr 3+ , Mo 3+ , W 3+ , Mn 3+ , Mn 2+ , Re 3+ , Re 2+ , Fe 3+ , Fe 2+ , Ru 3+ , Ru 2+ , Os 3+ , Os 2+ , Co 3+ , Co 2+ , Rh 2+ , Rh + , Ir 2+ , Ir + , Ni 2+ , Ni + , Pd 2+ , Pd + , Pt 2+ , Pt + , Cu 2+ , Cu + , Ag + , Au + , Zn 2+ , Cd2+ , Hg 2+ , Al 3+ , Ga 3+ , In 3+ , Tl 3+ , Si 4+ , Si 2+ , Ge 4+ , Ge 2+ , Sn 4+ , Sn 2+ , Pb 4+ , Pb 2+ , As 5+ , As 3+ , As + , Sb 5+ , Sb 3+ , Sb + , Bi 5+ , Bi 3+ , Bi + , B.E. 2+ , The term metal ion refers to both metal and metalloid ions. In some embodiments, metal ions suitable for use in preparing MOF materials include, along with the counter anion of the corresponding metal salt, Sc 3+ , Ti 4+ , V 4+ , V 3+ , V 2+ , Cr 3+ , Mo 3+ , Mg 2+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Ru 3+ , Ru 2+ , Os 3+ , Os 2+ , Co 3+ , Co 2+ , Rh 2+ , Rh + , Ir 2+ , Ir + , Ni 2+ , Ni + , Pd 2+ , Pd + , Pt 2+ , Pt + , Cu 2+ , Cu + , Ag+ , Au + , Zn 2+ , Cd 2+ , Al 3+ , Ga 3+ , In 3+ , Ge 4+ , Ge 2+ , Sn 4+ , Sn 2+ , Pb 4+ , Pb 2+ , Sb 5+ , Sb 3+ , Sb + , Bi 5+ , Bi 3+ , Bi + , and / or Be 2+ , In some embodiments, the metal ions for use in making the MOF materials can include, together with the counter ions of the corresponding metal salts: Sc 3+ , Ti 4+ , V 4+ , V 3+ , Cr 3+ , Mo 3+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Co 3+ , Co 2+ , Ni 2+ , Ni + , Cu 2+ , Cu + , Ag + , Zn 2+ , Cd 2+ , Al 3+ , Sn 4+ , Sn 2+ , Bi 5+ , Bi 3+ , and / or Bi + , In some embodiments, the metal ions for use in making the MOF materials include, together with the counter ions of the corresponding metal salts, Mg 2+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Co 3+ , Co2+ , Ni 2+ , Ni + , Cu 2+ , Cu + , Pt 2+ , Ag + , and Zn 2+ , is selected from the group consisting of: Fabrication of MOF materials
[0047] The synthesis of rigid and stable MOF materials can be carried out under very mild reaction conditions. In many cases, the reagents are combined in aqueous or non-aqueous solutions and the synthesis reaction temperatures are between 0°C and 100°C (in open beakers). In other cases, solution reactions are carried out in closed vessels at temperatures between 25°C and 300°C. In all cases, large single- or microcrystalline microporous solids are formed.
[0048] In the preparation of MOF materials, the reactants can be added in a molar ratio of metal ions to polydentate functional group-containing ligands of 1:10 to 10:1. In some embodiments, the metal ions to polydentate functional group-containing ligands are 1:3 to 3:1, such as 1:2 to 2:1. The amount of template agent may not affect the preparation of MOF materials, and in fact, the template agent may be employed as a solvent in which the reaction is carried out in some circumstances. Thus, large amounts of template agent can be used without interfering with the reaction or preparation of MOF materials. Furthermore, when a monodentate functional group-containing ligand and a polydentate functional group-containing ligand are used in combination with a metal ion, the monodentate functional group-containing ligand may be utilized in excess. In certain circumstances, the monodentate functional group-containing ligand may be utilized as a solvent in which the reaction is carried out. Furthermore, in certain circumstances, the template agent and the monodentate functional group-containing ligand may be the same. An example of a template agent that is a monovalent functional group-containing ligand is pyridine.
[0049] The preparation of MOF materials may be carried out in either aqueous or non-aqueous systems. The solvent may be polar or non-polar, a template agent, or any ligand containing a monodentate functional group. Examples of non-aqueous solvents include n-alkanes such as pentane, hexane, benzene, toluene, xylene, chlorobenzene, nitrobenzene, cyanobenzene, aniline, naphthalene, naphtha, n-alcohols such as methanol, ethanol, n-propanol, isopropanol, isopropanol, acetone, 1,2,-dichloroethane, methylene chloride, chloroform, carbon tetrachloride, tetrahydrofuran, dimethylformamide, dimethylsulfoxide, thiophene, pyridine, ethanolamine, triethylamine, ethylenediamine, etc. A suitable solvent may be selected based on the solubility of the starting reactants, and the choice of solvent may not be critical to obtaining the MOF material.
[0050] To aid in the formation of large single crystals of microporous materials suitable for single crystal X-ray structure analysis, solution reactions may be carried out in the presence of viscous materials such as polymer additives. Specific additives include polyethylene oxide, polymethylmethacrylate, silica gel, agar, fats and oils, and collagen, which may aid in achieving high yields and pure crystalline products. Growing large single crystals of microporous materials allows for unambiguous characterization of the microporous framework. Large single crystals of microporous materials may be useful for magnetic and electronic sensing applications.
[0051] Provided herein is a method for producing a MOF extrudate using the above-described MOF material, which comprises mixing the MOF material with an extrusion aid to form a MOF extrusion mixture, and extruding the MOF extrusion mixture to form a MOF extrudate.
[0052] To form extrudates of MOFs, the extruder may be a ram extruder (also called an extrusion press), a screw extruder. In a ram extruder, the MOF material is forced through a die by a mechanically or hydraulically actuated plunger or piston. In a screw extruder, a rotating screw, such as an auger, conveys the MOF material from a feed point to a die. After formation, the MOF extrudates may be dried and calcined as described herein.
[0053] In general, an extruder is a mechanical device used to produce extrudates with a defined cross-sectional shape. Extruders usually include a hopper that feeds the raw materials, a barrel or other confinement where the raw materials are combined, and a die with a die opening where the extrudate is formed. The material, forced to be homogenized by temperature, pressure, and shear in the barrel, is forced through a die opening with various cross-sectional shapes. The shape of the MOF extrudate can be rods or ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycomb bodies, granules, or similar shapes.
[0054] As described herein, the MOF material used in the present method is combined with one or more extrusion aids, and optionally additives that can modify various physical properties of the extrudate. The additives can be combined with the MOF material prior to or during extrusion. Exemplary extruders and extrusion processes for other types of extrudates are described in more detail in U.S. Pat. No. 4,441,990 (column 12, line 23 to column 19, line 64), which is incorporated herein by reference, and U.S. Pat. No. 6,517,807 (column 5, lines 35-50), which is incorporated herein by reference.
[0055] The extrusion method according to the present disclosure can include mixing or co-feeding the MOF material with one or more extrusion aids that allow for the extrusion of the MOFs at lower operating pressures and / or improve the mechanical properties of the MOF extrudate. The extrusion process can be performed with or without any solvent or solvent mixture. In some embodiments, the MOF extrudate exhibits substantially the same or improved physical qualities as the original MOF material, exhibiting surface area and mechanical strength suitable for commercial applications. Extrusion aids include liquid extrusion aids, solid extrusion aids, and polymeric aids that reduce the pressure during MOF extrusion and preserve or improve structural properties such as crystallinity, porosity, etc. of the starting MOF material.
[0056] As used in the present method and as shown in the examples below, extrusion aids are used to reduce pressure during the extrusion process and are also beneficial for maintaining certain operating pressures within limits in large-scale extruders. In embodiments, the extrusion aids can include materials that remain in the MOF extrudate as well as materials that do not remain in the MOF extrudate and are removed after extrusion by washing and / or aging. Extrusion aids can also improve the mechanical stability of a wide range of MOF materials with different metal nodes, pore structures, and crystallite sizes. As a result, the present method is applicable to a variety of MOF crystals and extrusion aid types. Overall, extrusion aids as used in the present method provide reduced MOF deformation during extrusion, increased surface area of the MOF extrudate, and increased crush strength of the MOF extrudate. Extrusion Aids
[0057] As described herein, the MOF extrudates of the present disclosure comprise at least one MOF material and at least one extrusion aid. As provided herein, the extrusion aid can be a liquid extrusion aid, a solid extrusion aid, and / or a polymeric extrusion aid. In the present method, the extrusion aid serves to reduce the pressure in the extruder and during the extrusion process, thereby minimizing or eliminating mechanical deformation and / or reduction in surface area of the MOF material. The extrusion aid is used in the present method to enable the production of MOF extrudates that may be damaged by extrusion. Liquid Extrusion Aids
[0058] As provided herein, the liquid extrusion aid includes water and linear and branched alkyl alcohols having an alkyl chain with at least two carbons. In embodiments, the liquid extrusion aid includes C3-C6 alcohols including 1-propanol, iso-propanol, 1-butanol, iso-butanol, 1-hexanol, 1-heptanol, and the like. 10 In an embodiment, the alkyl alcohols may include C 10 Liquid extrusion aids with higher carbon numbers can be used if the compound remains liquid and can be combined with the MOF material.
[0059] A method for producing a MOF extrudate includes mixing a MOF material with water alone and / or with one or more extrusion aids to form a MOF extrusion mixture. Optionally, a solvent can be used instead of water. In an embodiment, the MOF extrusion mixture can include water in a volume percent (vol%) ranging from about 0.5% to 95% by volume. Solid Extrusion Aids
[0060] Examples of solid extrusion aids include graphite and clays such as montmorillonite, kaolin, bentonite, halloysite, dickite, nacrite, and anorthite. Graphite has a specific surface area of 0. G (For example, about 3 to 8 m 2 / g or more), particle size D 50 It can be characterized in that the diameter is about 45 to 150 μm or less. 50 means that 50% of the particles are smaller than the stated value. For purposes of use in this method, graphite includes natural graphite, synthetic graphite, and graphite modifications including expanded graphite, graphite intercalation compounds, graphite nanofibers (GNF) or carbon nanotubes (CNT), and mixtures thereof. Graphite is available with a variety of properties from a number of manufacturers and suppliers.
[0061] In an embodiment, the solid extrusion aid is 10+Solid organic acids and their salts, such as magnesium stearate, can also be included. Solid extrusion aids can also include saturated and unsaturated C 10+ Contains organic acids.
[0062] The solid extrusion aid is combined with the MOF material in a weight percent (wt %) range of about 0.5 wt % to about 30 wt %, about 1 wt % to about 40 wt %, about 5 wt % to about 30 wt %. Polymer Extrusion Aids
[0063] The present method of producing MOF extrudates can include mixing the MOF material with one or more polymeric extrusion aids. The polymeric extrusion aids can be polar polymers, including homopolymers and copolymers of esters, amides, acetates, anhydrides, and the like, for example, C2-C6, such as ethylene and / or propylene and / or butene. 20 and copolymers of olefins and one or more polar monomers, such as acetates, anhydrides, esters, alcohols, and / or acrylics. Further examples of polymeric extrusion aids include polyesters, polyamides, ethylene vinyl acetate copolymers, polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl amine or derivatives thereof, and the like. In an embodiment, the polymeric extrusion aid comprises polyvinyl alcohol or a derivative thereof, such as polyvinyl alcohol, polyvinyl acetate, polyvinyl butyrate, or polypropionate.
[0064] In one embodiment, the polymer extrusion aid is a polymer blend of two or more polymers. The polymer extrusion aid can include a mixture of polymers in which a first polymer is present in a weight percent (wt%) range of about 10% to about 99% by weight of the polymer mixture, such as 20% to 95%, 30% to 90%, 40% to 90%, or 50% to 90% by weight, with the remainder being a second polymer or combination of polymers. In an embodiment, the polymer extrusion aid comprises a polymer blend of polyvinyl alcohol and polyvinyl acetate.
[0065] The disclosed method of making MOF extrudates includes mixing a MOF material with one or more polymeric extrusion aids to form a MOF extrusion mixture. In embodiments, the MOF extrusion mixture can include at least a polymer or polymer blend. The MOF material and polymeric extrusion aid can be mixed with an optional solvent and, optionally, one or more polymeric extrusion aids. In embodiments, the extrusion mixture can include a ratio of polyvinyl acetate to water in the range of 1:1 to 1:3. Extrusion Aid Blend
[0066] Blends of extrusion aids ("extrusion aid blends") can be made by mixing one or more polymers (as described above), by connecting reactors in series to make a reactor blend, or by using more than one catalyst to produce multiple types of polymers in the same reactor. In the case of blends, two or more extrusion aids can be mixed together before entering the extruder, or can be mixed in the extruder before being mixed with the MOF material.
[0067] The extrusion aid blend can be formed in any suitable equipment and manner, for example, by dry blending the individual components followed by melt mixing in a mixer, or by mixing the components together directly in a single or twin screw extruder which can include, for example, a Banbury mixer, a Haake mixer, a Brabender internal mixer, or compounding extruders and side arm extruders used directly downstream of the polymerization process, including blending of powders or pellets of the resins in the hopper of a film extruder. Optional Additives
[0068] Additionally, the MOF extrudates can be formulated with additives, such as fillers, antioxidants (e.g., hindered phenols such as IRGANOX® 1010 or IRGANOX® 1076, available from Ciba-Geigy), phosphites (e.g., IRGAFOS® 168, available from Ciba-Geigy), anti-agglomerating agents, adhesives such as polybutene, terpene resins, aliphatic and aromatic hydrocarbon resins, alkali metal and glycerol stearates, and hydrogenated rosins, UV stabilizers, heat stabilizers, antiblocking agents, release agents, antistatic agents, pigments, colorants, dyes, waxes, silica, fillers, and talc.
[0069] Other optional additives include precipitated silica or silica derived from by-products such as fly ash, e.g., silica-alumina, silica-calcium particles, fumed silica, etc. In certain embodiments, the silica is a particulate material and has an average particle size of 10 μm or less, e.g., 5 μm or less, or 1 μm or less. In one embodiment, the silica is amorphous silica.
[0070] Other additives include inorganic compounds such as titanium dioxide, hydrated titanium oxide, hydrated alumina or alumina derivatives, mixtures of silicon and aluminum compounds, silicon compounds, clay minerals, alkoxysilanes, amphiphilic substances, etc. The additives may also include compounds suitable for adhesion of powdered materials such as oxides of silicon, aluminum, boron, phosphorus, zirconium, titanium, etc. Furthermore, the additives may include oxides of magnesium and oxides of beryllium. Furthermore, tetraalkoxysilanes may be used as additives, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, similar tetraalkoxytitanium, tetraalkoxyzirconium compounds, trimethoxy-, triethoxy-, tripropoxy-, tributoxy-aluminum, etc.
[0071] The additives can have a concentration of between 0% and about 40% by weight, and between about 20% and about 40% by weight, based on the total weight of the one or more extrusion aids. Manufacturing process for MOF extrudates
[0072] As described herein, the method includes mixing the MOF material with an extrusion aid and optionally other additives to form an extrusion mixture. The method also includes extruding the extrusion mixture to form a MOF extrudate. The method of producing the MOF extrudate of the present disclosure includes producing a granule, i.e., a molded body. Thus, in certain embodiments, the MOF extrudate is formed and molded or granulated to form a granule or a shaped body.
[0073] The method may further include washing the extrudates with an optional solvent and may include drying and / or calcining the MOF extrudates. The optional solvent may include water, alcohols, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof. In certain embodiments, the optional solvent is selected from the group consisting of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, and combinations thereof. In certain embodiments, the optional solvent is water. In certain embodiments, the optional solvent is a mixture of two or more solvents. The optional solvent may be used to wash the MOF material and / or the MOF extrudates at different stages of the method.
[0074] The mixing step can be carried out in any suitable manner, including, for example, dry blending the individual components and then melt mixing in a mixer, or mixing the components together directly in a mixer, such as a Banbury mixer, Haake mixer, or Brabender internal mixer. Examples include high shear mixers, drum mixers, or single or twin screw extruders (which can include compound extruders and side arm extruders used directly downstream of the polymerization process and can include mixing of powder or pellets of the MOF material in the hopper of the extruder). In certain embodiments, the mixing and extruding steps are simultaneous, such as when the MOF material and extrusion aid are mixed and extruded in an extruder. Alternatively, the MOF material and extrusion aid are mixed with any solvent and then extruded.
[0075] The MOF material and extrusion aid can be premixed as dry ingredients. The order of addition of the components (MOF material, extrusion aid, optional solvent) will depend on the materials of interest. The order of addition of the extrusion aid, MOF material, and optional solvent does not matter, but the optimal order will be determined by the type of mixer used.
[0076] As described herein, the mixing step can be accomplished by methods of material processing or unit operations. Stirring can be used when mixing in liquid phase, and kneading and / or extrusion can be used when the mass to be mixed is in paste form. Solid components or powders can be mixed in a mixer. Also, depending on the condition of the parts used, atomizers, sprayers, diffusers, and nebulizers can be used. For MOF materials in paste or powder form, it is desirable to use static mixers, planetary mixers, mixers with rotating vessels, pan mixers, pug mills, shearing disk mixers, centrifugal mixers, sand mills, trough kneaders, internal mixers, internal kneaders, continuous kneaders, and the like. The mixing step may be sufficient to achieve molding or extrusion, such as when mixing and extrusion are performed simultaneously.
[0077] Furthermore, the mixing step can be continuous or batch-wise. When the mixing is batch-wise, the method can be carried out in a Z-arm mixer, or a cam-equipped mixer, or another type of mixer, such as a planetary mixer. The mixing step can provide a homogenous mixture of the powdered ingredients. The mixing can be carried out for 5-60 minutes, such as 10-50 minutes, with a maximum mixing time of 60 minutes or less being preferred. The rotation speed of the mixer arm can be 10-75 rpm, such as 25-50 rpm.
[0078] The MOF extrusion mixture can include 1 wt% to 99 wt%, e.g., 5 wt% to 99 wt%, 7 wt% to 99 wt%, or 10 wt% to 95 wt% MOF material; 1 wt% to 99 wt%, e.g., 1 wt% to 90 wt%, 1 wt% to 50 wt%, or 1 wt% to 20 wt% extrusion aid (including any additives); and optionally 0 wt% to 20 wt%, e.g., 1 wt% to 15 wt%, 1 wt% to 10 wt%, or 1 wt% to 7 wt% solvent. The weight percentages are expressed with respect to the total amount of compound and / or powder in the mixture, with the sum of the amounts of each of the compound and powder in the mixture equaling 100%. In some embodiments, the MOF extrusion mixture includes about 20 wt% to about 70 wt% solids, based on the total weight of the mixture.
[0079] In this method, the extrusion step (extrusion step) can be carried out in a single or twin screw ram extruder. If the step of preparing the MOF material is carried out continuously with the extrusion, the mixing can be coupled with the extrusion in one or more devices. According to this embodiment, the extrusion of the MOF extrusion mixture, also called "kneaded paste", can be carried out either directly at the end of a twin screw continuous mixer, for example, or by one or more batch type mixers connected to the extruder. The shape of the die that gives the shape to the extrudate can be selected from any suitable die, such as cylindrical, multi-lobed, grooved, slit, etc.
[0080] Extrusion can be influenced by the amount of extrusion aid and optional solvent added, and can be adjusted to obtain a mixture or paste that does not flow or dry excessively, allowing its extrusion under appropriate pressure conditions that depend on the extrusion equipment used. In some embodiments, extrusion is carried out at an extrusion pressure of about 1 MPa or more, for example, from about 0.1 MPa to about 20 MPa, from about 2 MPa to about 15 MPa, or from about 3 MPa to about 10 MPa.
[0081] The MOF extrudates include pelletized ones, and the product may be in the form of MOF extrudates or MOF extrudate pellets, although it is not excluded that the obtained MOF material is introduced into a surface rounding or spheronizing device, such as, for example, a tumbler.
[0082] The MOF extrudates may have a diameter of about 1 to about 10 mm, for example, about 1.5 to about 5 mm. In some embodiments, the mixture is extruded through a die having a diameter of about 0.01 mm to about 50 mm, for example, about 0.05 mm to about 40 mm, about 0.1 mm to about 20 mm, about 0.2 mm to about 10 mm, or about 0.5 mm to about 7 mm. Such extrusion molding equipment is described, for example, in Ullmann's Enzylopadie der Technischen Chemie, 4th Edition, Vol. 2, p. 295, 1972, etc. In addition to using an extruder, an extrusion press can also be used.
[0083] The MOF extrudates may optionally be aged, such as by drying or solidifying the MOF extrudates. Aging may include a temperature of about 0° C. to about 300° C., such as about 20° C. to about 200° C., or about 20° C. to about 150° C. Aging may be performed for a period of about 1 minute to about 72 hours, such as about 30 minutes to about 72 hours, about 1 hour to about 48 hours, or about 1 hour to about 24 hours. In some embodiments, aging may be performed in air or humidified air having a relative humidity of 20% to 100%, such as 70% to 100%. Treatment with humidified gas allows for hydration of the material and may be beneficial for solidification of certain extrusion aids. In some embodiments, aging is performed in dehumidified air or inert gas, such as air having a relative humidity of 0% to 10%, or 0% to 5%.
[0084] The MOF extrudates or mature MOF extrudates can also be optionally activated. Activation can be carried out at a temperature of about 50°C to about 500°C, for example, about 100°C to about 300°C. Activation can be carried out for a period of about 1 hour ("h") to about 6 hours, for example, about 1 hour to about 4 hours. Activation can aid in the removal of the solvent used to facilitate the extrusion of the mixture. Activation can be carried out in air, an inert gas, or a gas mixture containing oxygen. Additionally, activation can be carried out under reduced or increased pressure, such as in a vacuum or at a pressure higher than atmospheric pressure. In certain embodiments, the extrudates are calcined under dry air or air with different levels of humidity, or they are heat treated in the presence of a gas mixture containing an inert gas, such as nitrogen and / or oxygen. In certain embodiments, the gas mixture used can contain 5% by volume or more, for example 10% by volume or more, of oxygen. In alternative embodiments, the gas mixture is free or substantially free of oxygen and contains only inert gases. The calcination temperature can be from about 50°C to about the decomposition temperature of the MOF material. Properties of MOF extrudates
[0085] The MOF extrudates produced by the present method may have a bulk crush strength of about 0.2 lb-force to about 80 lb-force, e.g., about 0.4 lb-force to about 50 lb-force, about 1 lb-force to about 20 lb-force, or about 4 lb-force to about 15 lb-force. Crush strength may be related to extrudate size, and the extrudate may have features that extend up to about 1 mm or more in each direction in space. Bulk crush strength is a standardized test (ASTM D7084-04).
[0086] The MOF extrudates produced by this method have a BET surface area (measured using ASTM D3663) of about 50 m 2 / g ~ approx. 4,000m 2 / g, approx. 50m 2 / g ~ approx. 3,000m 2 / g, approx. 50m 2 / g ~ approx. 2,000m 2 / g, about 100m 2 / g ~ approx. 1,800m 2 / g, about 100m 2 / g ~ approx. 1,700m 2 / g, about 100m 2 / g ~ approx. 1,600m 2 / g, about 100m 2 / g ~ approx. 1,550m 2 / g, about 100m 2 / g ~ approx. 1,500m 2 / g, about 100m 2 / g ~ approx. 1,450m 2 / g, about 100m 2 / g ~ approx. 1,400m 2 / g, about 100m 2 / g ~ approx. 1,300m 2 / g, about 100m 2 / g ~ approx. 1,250m 2 / g, about 100m 2 / g ~ approx. 1,200m 2 / g, about 100m 2 / g ~ approx. 1,150m 2 / g, about 100m 2 / g ~ approx. 1,100m 2 / g, about 100m 2 / g ~ approx. 1,050m2 / g, about 100m 2 / g~about 1,000m 2 / g, about 100m 2 / g~about 900m 2 / g, about 100m 2 / g~about 850m 2 / g, about 100m 2 / g~about 800m 2 / g, about 100m 2 / g~about 700m 2 / g, about 100m 2 / g~about 600m 2 / g, about 100m 2 / g~about 550m 2 / g, about 100m 2 / g~about 500m 2 / g, about 100m 2 / g~about 450m 2 / g, about 100m 2 / g~about 400m 2 / g, about 100m 2 / g~about 300m 2 / g, about 100m 2 / g~about 200m 2 / g, about 300m 2 / g~about 1,800m 2 / g, about 300m 2 / g~about 1,700m 2 / g, about 300m 2 / g~about 1,600m 2 / g, about 300m 2 / g~about 1,550m 2 / g, about 300m 2 / g~about 1,500m 2 / g, about 300m 2 / g~about 1,450m 2 / g, about 300m 2 / g~about 1,400m 2 / g, about 300m 2 / g~about 1,300m 2 / g, about 300m 2 / g~about 1,250m 2 / g, about 300m 2 / g~about 1,200m 2 / g, about 300m 2 / g~about 1,150m 2 / g, approx. 300m 2 / g ~ approx. 1,100m 2 / g, approx. 300m 2 / g ~ approx. 1,050m 2 / g, approx. 300m 2 / g ~ approx. 1,000m 2 / g, approx. 300m 2 / g ~ approx. 900m 2 / g, approx. 300m 2 / g~about 850m 2 / g, approx. 300m 2 / g~about 800m 2 / g, approx. 300m 2 / g~about 700m 2 / g, approx. 300m 2 / g~about 600m 2 / g, approx. 300m 2 / g ~ approx. 550m 2 / g, approx. 300m 2 / g~about 500m 2 / g, approx. 300m 2 / g ~ approx. 450m 2 / g, or about 300m 2 / g~about 400m 2 In particular, the MOF extrudate may have a molecular weight of about 300 m 2 / g ~ approx. 4,000m 2 / g, for example, about 500m 2 / g ~ approx. 1,600m 2 / g total BET surface area.
[0087] Additionally, the MOF extrudates produced by the present method may have a comparative BET surface area of about 30% to about 100%, such as about 50% to about 95%, or about 70% to about 90% (measured using ASTM D3663) of the raw (raw) MOF. Comparative BET surface area is defined as the BET surface area of the MOF extrudate divided by the BET surface area of the MOF material. For example, HKUST-1 was used to prepare the MOF extrudate and the MOF extrudate had a comparative BET surface area of 1292 m 2 / g BET surface area of 1292 m 2 / g is 1615m 2 / g (the calculated BET surface area of HKUST-1), the MOF extrudates have a comparative BET surface area of 80%.
[0088] The MOF extrudates produced by this method have a pore volume (measured using ASTM D3663) of about 0 cm 3 / g ~ approx. 1.6cm 3 / g, approx. 0.2cm 2 / g ~ approx. 1.6cm 2 / g, 6cm 3 / g, approx. 0.2cm 2 / g ~ approx. 1.5cm 3 / g, approx. 0.2cm 3 / g ~ approx. 1.4cm 3 / g, approx. 0.2cm 3 / g ~ approx. 1.3cm 3 / g, approx. 0.3cm 3 / g ~ approx. 1.2cm 3 / g, approx. 0.3cm 3 / g ~ approx. 1.cm 3 / g, approx. 0.4cm 3 / g ~ approx. 1.1cm 3 / g, or about 0.4 cm 3 / g ~ approx. 1cm 3 The MOF extrudates may have a porosity of about 30% to about 100%, such as about 50% to about 95%, or about 70% to about 90% (measured using ASTM D3663) of the raw MOF material.
[0089] The MOF extrudates produced by the present method may have an average pore size (measured using ASTM D4365) of from about 1 Å to about 40 Å, such as from about 2 Å to about 25 Å, or from about 6 Å to about 23 Å. Purpose
[0090] The MOF extrudates can be used in applications such as catalysis, separation, purification, capture, etc. For example, the MOF extrudates can be contacted with a gaseous feedstock to be treated in a reactor, either a fixed bed reactor, or a radial reactor, or a fluidized bed reactor or an absorption bed. For use in the fields of catalysis and separation, the expected value of ACS is 0.9 daN / mm or more, for example 1 daN / mm or more. Thus, the described MOF extrudates have sufficient mechanical strength to be used in the fields of catalysis and separation.
[0091] MOF extrudates can be used in processes where porosity and flow channels are advantageous over solids or powders, including as catalysts, catalyst supports, adsorption, fluid storage, desiccants, ion exchange materials, molecular sieves (separators), materials for chromatography, materials for selective release and / or uptake of molecules, molecular recognition, nanotubes, and nanoreactors.
[0092] In some embodiments of the application, the MOF extrudates are used as catalysts in fixed bed / packed bed reactors. In principle, the MOF extrudates may be used in gas-phase reactions or in liquid-phase reactions, where the solid forms are suspended in a slurry. Furthermore, the MOF extrudates can be used to catalyze a variety of reactions where the presence of channels and / or pores incorporated therein is known or believed to enhance the activity and / or selectivity and / or yield of the reaction.
[0093] They also have applications in the storage of chemical compounds, especially gaseous compounds: the small pore size and porosity of MOF extrudates may enable superior storage or sequestration of gaseous compounds such as CO2, CH4, or H2, which are of particular interest to the energy industry, as well as gas separation.
[0094] Features of the present invention are illustrated in the following non-limiting examples. EXAMPLES
[0095] The metal-organic framework HKUST-1 (Cu3btc2, where btc is 1,3,5-benzenetricarboxylate) was prepared in a mixture of water and one of the liquid extrusion aids, an alkyl alcohol (1-propanol, 1-butanol, 1-hexanol). Ethanol was used as the alcohol additive for comparison.
[0096] 1-Propanol was mixed with water and then added to the extrusion-ready MAL-MIX (hereafter referred to as MOF material); 1-butanol and 1-hexanol were added separately as they are not water-soluble. All experiments were performed with a 1:1 ratio of water to alcohol. All MAL-MIX was extruded at 43% solids in a ram extruder (commonly called high temperature melt extruder (HTME)). P1, P2, and P3 are the pressures measured during extrusion at the beginning, middle, and end of extrusion. The results of this experiment are shown in Table 1 below. It shows that the pressure during extrusion can be reduced by using a long-chain alcohol as an extrusion aid, specifically as a liquid extrusion aid. [Table 1]
[0097] As shown in Table 1, all three alcohols reduced the pressure compared to ethanol, with 1-hexanol being the most notable. The longer carbon chains of the longer alcohols likely provide more lubrication during the extrusion process, resulting in these lower pressures.
[0098] FIG. 1 shows the retention of crystallinity for the MOF, HKUST-1, extruded with each of the long-chain alcohols, and FIG. 2 shows the N2 adsorption isotherms used to determine the BET surface area of each of the extruded materials.
[0099] Furthermore, the pressure during extrusion could be further reduced by using graphite as an extrusion aid. Similar to long-chain alcohols, it is a solid extrusion aid that can reduce the pressure during extrusion. Specifically, as a lubricant when pelletizing graphite (20 μm or less), experiments were performed in which 2% and 20% graphite pellets were pressed at 500 psi and 1000 psi, respectively. The resulting surface areas were compared to that of HKUST-1 powder and weighted to account for the lack of surface area of the graphite. When mixed, the graphite appeared to coat the outer surface of the HKUST-1 particles. A comparison of BET surface areas is shown in Table 2 immediately below. [Table 2]
[0100] In Table 2, the percentage of graphite represents the weight percent of the total solids weight, for example, 2 wt% graphite means that 2% of the solids is graphite and 98% of the solids is HKUST-1 powder or MOF material.
[0101] Based on the success of the pelletization experiments, HKUST-1 was extruded with graphite to observe the pressure change as a function of graphite content (GJM-2016-33584, MTK-026). Samples were extruded through a 1 / 16” (inch) cylindrical die in an HTME hand press. The 2% graphite sample did not reduce the extrusion pressure and retained most of the surface area of HKUST-1. The inclusion of 20% graphite allowed for a significant reduction in pressure, which is also significantly lower than the pressure required for the same solids content without graphite (GJM-2016-33396, MTK-017). Additionally, the surface area weighted to account for graphite was 1327 m 2 / g retains 94% of the surface area, indicating that the graphite does not block the pores of the HKUST-1 material. By using less than 20 wt.% graphite, the pressure in the extruder can be reduced while still maintaining the properties of the metal-organic framework in the extrudate.
[0102] Polyvinyl alcohol (PVA) was also tested as an extrusion aid. Both ZIF-8 and HKUST-1 used PVA as the polymer extrusion aid. It was shown that the addition of small amounts of polyvinyl alcohol with polyvinyl acetate as the binder improved the crush strength. For example, the crush strength of HKUST-1 increased from 53 lbf / in to 213 lbf / in with the addition of 2 wt% polyvinyl alcohol, and the surface area was also significantly preserved compared to the case without polyvinyl alcohol. Table 4 shows the crush strength and BET surface area of these two metal-organic frameworks (PVA: polyvinyl alcohol, PVAc / DI: polyvinyl acetate / deionized water (w / w)). The crush strength of the MOF extrudates was measured with a Varian VK200 according to ASTM D7084. The BET surface area was measured according to ASTM D3663. [Table 3]
[0103] Extrusion using polyvinyl alcohol (PVA) shows significantly higher crush strength compared to extrusion without PVA. PVA as an extrusion aid can improve the crush strength and at the same time improve the mechanical stability. Moreover, as demonstrated with various extrusion aids and various MOF materials with different metal nodes, pore sizes, and crystal structures, the inclusion of an extrusion aid does not negatively affect the crystallinity and surface area of the MOF material. In this disclosure, different types of extrusion aids for MOF materials are provided. Each extrusion aid has in common that it can be extruded while maintaining the quality and porosity of the MOF material, and can produce MOF extrudates with sufficient quality for industrial applications. For some MOFs, it is necessary to extrude with a mixture of water and ethanol to reduce the degradation of MOFs due to the heat of adsorption when exposed to liquid water. As mentioned above, by replacing ethanol with a long-chain alcohol, it was possible to obtain the same effect as ethanol and suppress the pressure increase during extrusion. In the extrusion of MOF materials, reduced pressure is crucial to maintain the crystallinity and porosity of MOFs under high pressure exposure. Additionally, large screw extruders used for large scale production of catalyst extrudates have pressure limitations that necessitate reduced pressure during extrusion.
[0104] As mentioned above, the extrusion of metal-organic frameworks is a relatively unexplored field, but one that is necessary to formulate these new materials and use them in a variety of applications. MOFs have low stiffness and can be damaged from the high pressures and high temperatures they are exposed to during extrusion. In addition, binders are often required to improve the mechanical strength of the resulting extrudates. However, many binders are incompatible with MOFs, mainly due to the lack of a compatible surface. Herein, we provide a method to produce MOF extrudates using different extrusion aids that reduce the pressure during extrusion while maintaining the structural integrity of the MOF material and improving the mechanical strength of the MOF extrudates. Interestingly, improved pressure reduction can be achieved by using both a solvent that does not remain in the final extrudate and a solid extrusion aid that remains in the final extrudate. The use of extrusion aids allows for a new and unconventional approach. Another aspect of the present invention is as follows. [1] mixing the metal-organic framework material with an extrusion aid to form a metal-organic framework extrusion mixture; and extruding the metal-organic framework mixture in an extruder to produce metal-organic framework extrudates; 1. A method for producing metal-organic framework extrudates in an extruder, comprising: A method for producing an extrudate, the pressure in the extruder being reduced by about 10% to about 55% compared to the pressure in the extruder when extruding a metal-organic framework material without an extrusion aid. [2] The method according to [1], wherein the extrusion aid is a liquid extrusion aid, a solid extrusion aid and / or a polymer extrusion aid. [3] Liquid extrusion aid is linear C 3 ~C 10 Alkyl alcohol or branched C 3 ~C 10 The method according to [2], wherein the alcohol is an alkyl alcohol. [4] The method according to [2], wherein the liquid extrusion aid is selected from the group consisting of 1-propanol, iso-propanol, 1-butanol, iso-butanol, 1-hexanol, 1-heptanol. [5] The extrusion aid according to [1], wherein the liquid extrusion aid comprises water in the range of about 0.1% by volume to 95% by volume. [6] The method according to [2], wherein the solid extrusion aid is graphite. [7] The method according to [2], wherein the solid extrusion aid is magnesium stearate. [8] Solid extrusion aid is saturated or unsaturated C 10+ The method according to [2], wherein the compound is an organic acid or a salt thereof. [9] The method according to [2], wherein the solid extrusion aid is mixed with the metal-organic framework in a range of about 1 wt % to about 30 wt %.
[10] The method according to any one of [1] to [9], wherein the polymer extrusion aid is polyvinylamide, polyacrylate, polycarbonate, polyamide, polyester, polyether, polyvinylamine, polyvinyl alcohol, polyvinyl ester, or a combination thereof.
[11] The method according to [2], wherein the polymer extrusion aid is polyvinyl alcohol.
[12] The method according to any one of [1] to
[11] , wherein the metal-organic framework mixture comprises about 0.5 wt % to 10 wt % polyvinyl alcohol.
[13] The method according to any one of [1] to
[12] , wherein the metal-organic framework mixture comprises polyvinyl acetate and water, and the ratio of polyvinyl acetate to water is from about 1:1 to about 1:3.
[14] The method according to any one of [1] to
[13] , wherein the metal-organic framework extrudates are shaped as rods, ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycomb bodies, or granules.
[15] The metal-organic framework materials were HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, and M 2 (m-dobdc), MOF-274, Cu(Qc)2 The method according to any one of [1] to
[14] , selected from the group consisting of and combinations thereof.
[16] The metal-organic framework material is a substructure of an alkyl group having 1 to 10 carbon atoms; or A partial structure of an aryl group having 1 to 5 aromatic rings, (wherein one or more moieties each have at least two X groups, where X is a functional group configured to coordinate to a metal or metalloid.) The method according to any one of [1] to
[15] , comprising an organic ligand comprising one or more of:
[17] Each X is CO 2 H, OH, SH, OH 2 , N.H. 2 , CN, HCO, CS 2 H, NO 2 , S.O. 3 H, Si(OH) 3 , Ge(OH) 3 , Sn(OH) 3 , Si(SH) 4 , Ge(SH) 4 , Sn(SH) 3 , P.O. 3 H, AsO 3 H, AsO 4 H, P(SH) 3 , As(SH) 3 , CH(RSH) 2 , C(RSH) 3 , CH(RNH 2 ) 2 , C(RNH 2 ) 3 , CH(ROH) 2 , C(ROH) 3 , CH(RCN) 2 , C(RCN) 3 , CH(SH) 2 , C(SH) 3 , CH(NH 2 ) 2 , C(NH 2 ) 2 , CH(OH) 2 , C(OH) 3 , CH(CN) 2 , C(CN) 3 , a nitrogen-containing heterocycle, a sulfur-containing heterocycle, and combinations thereof, where R is an alkyl group having 1-5 carbon atoms or an aryl group consisting of 1-2 phenyl rings.
[18] The method according to any one of [1] to
[17] , wherein the organic ligand is selected from the group consisting of 1,3,5-benzenedicarboxylate, 1,4-benzenedicarboxylate, 1,3-benzenedicarboxylate, biphenyl-4,4'-dicarboxylate, benzene-1,3,5-tris(1H-tetrazole), acetylene-1,2-dicarboxylate, naphthalene carboxylate, adamantane tetracarboxylate, benzene tribenzoate, methane tetrabenzoate, adamantane tribenzoate, biphenyl-4,4'-dicarboxylate, imidazole, 2,5-dihydroxy-1,4-benzenedicarboxylic acid, 4,4'-dihydroxy-(1,1'-biphenyl)-3,3'-dicarboxylic acid, and combinations of derivatives thereof.
[19] Metal-organic framework material, metal-organic framework material, Be 2+ , Mg 2+ , Ca 2+ 、Sr 2+ , B.A. 2+ , Sc 3+ 、Y3+ , Ti 4+ 、Zr 4+ , Hf 4+ 、V 4+ 、V 3+ 、V 2+ , Nb 3+ , Ta 3+ 、Cr 3+ , Mo 3+ 、W 3+ , Mn 3+ , Mn 2+ , Re 3+ , Re 2+ , Fe 3+ , Fe 2+ , Ru 3+ , Ru 2+ , Os 3+ , Os 2+ , Co 3+ , Co 2+ , Rh 2+ , Rh + 、Ir 2+ 、Ir + , Ni 2+ , Ni + , Pd 2+ , Pd + , Pt 2+ , Pt + , Cu 2+ , Cu + , Ag + , Au + , Zn 2+ , Cd 2+ , Hg 2+ 、Al 3+ , Ga 3+ , In 3+ 、Tl 3+ , Si 4+ , Si 2+ , Ge 4+ , Ge 2+ , Sn 4+ , Sn 2+ , Pb 4+ , Pb 2+ , As 5+ , As 3+ , As + , Sb 5+ , Sb 3+ , Sb + , Bi 5+ , Bi 3+ , Bi + The method according to any one of [1] to
[18] , comprising a metal ion selected from the group consisting of:
[20] 20. The metal-organic framework extrudate according to any one of claims 1 to 19, wherein the metal-organic framework extrudate has a comparative BET surface area of about 40% to about 100% relative to the substrate prior to extrusion.
[21] The method according to any one of [1] to
[20] , further comprising the step of aging the metal-organic framework extrudates at a temperature of about 40° C. to about 150° C. for a period of about 30 minutes or more.
[22] The method according to any one of [1] to
[21] , further comprising calcining the metal-organic framework extrudates at a temperature of about 100° C. to about 300° C. for about 1 hour or more.
[23] The method according to any one of [1] to
[22] , wherein the step of extruding the metal-organic framework is carried out through a die having a diameter of about 0.01 mm to about 50 mm.
[24] The method according to any one of [1] to
[23] , further comprising washing the metal-organic framework extrudates with an optional solvent.
[25] The method according to any one of [1] to
[24] , wherein the optional solvent is selected from the group consisting of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof.
[26] The method according to any one of [1] to
[25] , wherein the MOF extrusion mixture contains about 20% by weight to about 70% by weight of solids, based on the total weight of the MOF extrusion mixture.
Claims
1. mixing the metal-organic framework material with an extrusion aid to form a metal-organic framework extrusion mixture; and extruding the metal-organic framework extrudate mixture through an extruder to produce metal-organic framework extrudates; 1. A method for producing metal-organic framework extrudates in an extruder, comprising: reducing the pressure in the extruder by 10% to 55% compared to the pressure in the extruder when extruding the metal-organic framework without the extrusion aid; the extrusion aid is a polymeric extrusion aid comprising polyvinyl alcohol and polyvinyl ester; A method for producing metal-organic framework extrudates, wherein the pressure in the extruder using an extrusion aid is between 0.1 MPa and 20 MPa.
2. 10. The method of claim 1, wherein the extruded metal-organic framework mixture comprises 0.5% to 10% by weight of polyvinyl alcohol.
3. 3. The method of claim 1 or 2, wherein the metal-organic framework extrusion mixture comprises polyvinyl acetate and water, and the ratio of polyvinyl acetate to water is from 1:1 to 1:
3.
4. The method according to any one of claims 1 to 3, wherein the metal-organic framework extrudates are shaped as rods, ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycomb bodies, or granules.
5. Metal-organic framework materials include HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, M 2 (m-dobdc), MOF-274, Cu(Qc) 2 and combinations thereof.
6. 6. The method of any one of claims 1 to 5, wherein the metal-organic framework extrudate has a comparative BET surface area of from 40% to 100% relative to the raw metal-organic framework prior to extrusion.
7. 7. The method of any one of claims 1 to 6, further comprising the step of ageing the metal-organic framework extrudates at a temperature between 40°C and 150°C for a period of at least 30 minutes and / or calcining the metal-organic framework extrudates at a temperature between 100°C and 300°C for at least 1 hour.
8. The method according to any one of claims 1 to 7, wherein the step of extruding the metal-organic framework extrusion mixture is carried out through a die having a diameter of from 0.01 mm to 50 mm.
9. The method of any one of claims 1 to 8, further comprising washing the metal-organic framework extrudates with a solvent.
10. 10. The method of claim 9, wherein the solvent is selected from the group consisting of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof.
11. 11. The method of any one of claims 1 to 10, wherein the extruded metal-organic framework mixture comprises 20 wt% to 70 wt% solids, based on the total weight of the extruded metal-organic framework mixture.
Citation Information
Patent Citations
MoFs adsorbent and application thereof
CN105056896A
Molded body containing metal-organic framework
JP2008518781A
Porous organometallic skeleton materials as desiccants
JP2011509825A
Crystalline porous inorganic hybrid and method for producing the same
JP2013511385A
Separation material made of porous metal complex composition
JP2015202470A